Quinolones for the Treatment of Neisseria Gonorrhoeae and Chlamydia Trachomatis - Sebastian Faro (Hindawi Limited, 1993)
The most commonly sexually transmitted bacteria are Neisseria gonorrhoeae and Chlamydia trachomatis. The quinolones ofloxacin and ciprofloxacin have been shown to have activity against both of these bacteria in vitro and in vivo. Ofloxacin is particularly well suited for the treatment of N. gonorrhoeae and C. trachomatis cervical infection, which can be considered the earliest manifestation of pelvic inflammatory disease (PID). Not only can ofloxacin be effectively used as a single agent, it is also useful in treating urinary tract infections caused by Enterobacteriaceae. Although it has moderate activity against anaerobes in general, ofloxacin does have activity against the anaerobes commonly isolated from female patients with soft tissue pelvic infections. Thus, ofloxacin has the potential for being utilized to treat early salpingitis.